Prenatal dilatation of the pulmonary artery in the third trimester – important information for paediatric cardiologist or for neonatologist? Case report - Murlewska, Julia; Pekasiewicz, Joanna; Respondek-Liberska, Maria (Prenatal Cardiology, 2019)
We present a case of dilated main pulmonary artery diameter with accompanying cardiac anomalies and postnatal follow-up. The abnormalities in the left side of the heart concerned the left superior vena cava (LSVC), decreased left ventricular contractility SF LV (shortening fraction), and narrowing/accelerating flows through the aortic valve and aortic arch isthmus. In our case, coarctation of the aorta was suspected both pre- and postnatally due to the dominant picture of the accelerated flow velocities, but the patient did not require neonatal surgery. Based on a retrospective review of the case, we tried to explain our prenatal and early postnatal findings. After the exclusion of the structural congenital heart defects as a base of the dilatation of the main pulmonary artery, we should consider other pathophysiological mechanisms presented in the following report.